2021
DOI: 10.3389/fpsyt.2021.655451
|View full text |Cite
|
Sign up to set email alerts
|

Autism-Associated Variant in the SLC6A3 Gene Alters the Oral Microbiome and Metabolism in a Murine Model

Abstract: Background: Altered dopamine (DA) signaling has been associated with autism spectrum disorder (ASD), a neurodevelopmental condition estimated to impact 1 in 54 children in the United States. There is growing evidence for alterations in both gastrointestinal function and oral microbiome composition in ASD. Recent work suggests that rare variants of the SLC6A3 gene encoding the DA transporter (DAT) identified in individuals with ASD result in structural and functional changes to the DAT. One such recently identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Furthermore, altered dopamine signaling has been associated with ASD in both mice and humans. A study by DiCarlo et al suggested that mice that are homozygous for the T356M DNA variant of the SLC6A3 gene, which encodes the dopamine transporter, manifests altered dopamine signaling and metabolic dysfunction, weigh less and have reduced body fat [ 89 ]. The authors found a significant decrease in Fusobacterium abundance at the oral level.…”
Section: Microbiota–gut–brain Axis Involvement In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, altered dopamine signaling has been associated with ASD in both mice and humans. A study by DiCarlo et al suggested that mice that are homozygous for the T356M DNA variant of the SLC6A3 gene, which encodes the dopamine transporter, manifests altered dopamine signaling and metabolic dysfunction, weigh less and have reduced body fat [ 89 ]. The authors found a significant decrease in Fusobacterium abundance at the oral level.…”
Section: Microbiota–gut–brain Axis Involvement In Asdmentioning
confidence: 99%
“…The authors found a significant decrease in Fusobacterium abundance at the oral level. Moreover, there is a positive association among Fusobacterium abundance, better glucose management and decreased body fat [ 89 ].…”
Section: Microbiota–gut–brain Axis Involvement In Asdmentioning
confidence: 99%
“…The link between the microbiome and depression has been proven by research on bacterial abnormalities in depressed patients. It has also been shown that feeding multiple microbiome populations (L. rhamnosus, B. infantis, B. longum) can improve mood even in healthy subjects (26,(31)(32)(33).…”
Section: Figure 1 Direct and Indirect Mechanisms Of Bacteria Infectin...mentioning
confidence: 99%
“…In addition, the oral microbiota of these mice are altered with lower Fusobacterium abundance, as well as glucose dysregulation. There was a positive association between Fusobacterium abundance and improved glucose handling as well as a decrease in body fat [ 151 ].…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%